IMPLEMENTATION OF NATIONAL CYBERSECURITY STRATEGIES: ECONOMIC AND POLITICAL ASPECT - Kotukh , Ye. V (Theory and Practice of Public Administration, 2021)
The issue of maintaining the critical infrastructure security is a matter of national security – with or without taking into account the cyber component. However, networks used in critical infrastructure are not immune to growing dependence on Internet technology. Therefore, it can be argued that cybersecurity is combined with national security mainly in critical infrastructure.In many developed countries, government agencies have been set up to deal with the security of information systems and the response to computer emergency incidents.The challenges of cybersecurity apply to all countries, and none of them faces exactly the same problems, but most of them are similar, making it possible to develop common universal solutions that can then be adapted to the conditions of specific countries. At the same time, cyberspace is an integral part of the development of any modern state, as powerful cyberspace is crucial for the progress and development of states in the economic, political and social spheres.This necessitates the development and implementation of national cybersecurity strategies that highlight and emphasize the need to raise awareness of cyberspace issues within heterogeneous categories, such as civil servants, politicians, businessmen, IT-professionals, members of the public, and others. And depending on the approaches used, cybersecurity can be seen either as the responsibility of the private sector, or as the responsibility of individual public authorities – from law enforcement to military agencies, or a combination of both. And the last approach, in our opinion, should be applied in Ukraine.